Infrastructure requirements analysis in developing intelligent system for k-farmer community - Risidi, Hanim; Abdullah, Rusli (2008)
Agriculture is a knowledge-intensive business, which offers farmers with a large volume of knowledge. However, often farmer do not use this facility to manage their knowledge. Knowledge management (KM) in agriculture promotes an integrated approach to the creation, capture, accessing and use of farmer domain knowledge of product, services and processes. New technologies expected can help farmers to achieve better knowledge management. In this paper, we have proposed the infrastructure requirement analysis in developing intelligent system for knowledge farmer community. Knowledge management initiative among farmers expected to produce more gain in their farm productions as well as return on investment (ROI). Thus, helps the community to become more productive and knowledgeable.